MANFAAT TEKNIK REBOZO TERHADAP PERSALINAN - T. Marzila Fahnawal; Prasida Yunita (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2022)
Childbirth is a series of processes that end with the production of the results of conception from intrauterine to extrauterine by the mother. Labor pain is a subjective experience of the physical sensations associated with uterine contractions, dilation and thinning of the cervix, as well as fetal decline during labor. The purpose of this study is to obtain scientific reference sources about utilizing rebozo techniques for childbirth based on the results of previous research. The research method by conducting a literature search conducted until January 2022 through the Pubmed database and google scholar using the keyword rebozo technique against childbirth using more than 30 articles as a reference source. Rebozo technique is a nonpharmacological way or without the use of (traditional) medicine to help manage pain during labor. Rebozo technique is done by wrapping the rebozo around the pelvis and buttocks of pregnant women, then shaking it during the labor process. The swing of the rebozo is considered able to relax the mother and help position the baby into the birth canal The rebozo technique is a practical non-invasive technique performed on women standing, lying down, or resting on their hands and knees. It involves the movement of a woman's hips that are gently controlled side by side using a special woven scarf and is performed well by midwives or other support people. Rebozo technique is usually done in pregnant women after 28 weeks of pregnancy, can also be carried out during labor.